A Bibliometric Analysis Examining the Adoption of Augmented Reality in Tourism Research - Tinesa Fara Prihandini; Mochammad Bruri Triyono; Priyanto (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This study aims to identify the use of Augmented Reality technology and the trend of usingAR in tourism with time limitation from 2013 until 2022. It also aims to determine the valuablecontributions of documents, sources, authors, countries, and institutions worldwide intourism. The qualitative method using bibliometric analysis is suitable for this study becauseit can provide an overview and classify. Data was collected from the Scopus database andthen analyzed using VOSviewer software. The results show that (1) museum, (2) sustainabletourism, and (3) heritage tourism are the keywords most often used in research. The potentialresearch of AR in tourism is directed at the development of underwater tourism, the applicationof virtual museums, ecotourism, culture heritage tourism, digital heritage and destinationimage. Sustainability (Switzerland), Current Issues in Tourism, and The International Journalof Human-Computer are the journals with the most publications. Tom Dieck M. C.M.C, JungT, and Chung N are authors with a high degree of collaboration with other authors. UnitedKingdom, Spain, and Italy became the countries with the highest publications. Researchtrends and advances in augmented reality in tourism have been discussed in more detail inthis paper.